We Appreciate Power: A Multimodal Critical Discourse Analysis of Grimes' Music Video Posted on YouTube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism.

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.